STUDY OF THE PHOTOCATALYTIC DEGRADATION OF A CATIONIC DYE IN AQUEOUS SOLUTION BY DIFFERENT TYPES OF CATALYSTS (Sciences & Technology. A, exactes sciences, 2014)
The photocatalytic degradation of an aqueous solution of Malachite Green Oxalate (MG) has been investigated using TiO2-P25, TiO2-PC100 and ZnO as catalysts in slurry form in presence of UV lamp at λmax= 365 nm. The adsorption of MG on TiO2-P25 and ZnO catalysts was found favorable by the Langmuir approach, while Freundlich equation represents better the adsorption of MG on the TiO2-PC100 surface. The disappearance of MG by photocatalysis in presence of the three catalysts followed pseudo first-order kinetics and Langmuir- Hinshelwood model is well suited to describe the kinetics of photocatalytic disappearance of these dye The effect of the initial dye concentration, type of catalysts, addition of alcohol such as tert-butyl and solution pH on the degradation of MG in presence of TiO2-P25, TiO2-PC100 or ZnO catalysts were discussed. The ZnO catalyst is more effective than TiO2-P25 and TiO2-PC100 at different operating conditions studied. COD analysis showed a complete mineralization of the dye in a relatively short time of about 2 h for ZnO, and a reduction of 42 % and 10 % in COD for TiO2-P25 and TiO2-PC100, respectively, after 2 h of irradiation.